Socio-economic and agroecological factors influencing sacha inchi productivity in West Java, Indonesia - MUHAMAD NURDIN YUSUF; DADI DADI; JETI RACHMAWATI; BENIDZAR M. ANDRIE; SAEPUL AZIZ; MOCHAMAD ARIEF RIZKI MAULADI (Smujo International, 2026)
Abstract. Yusuf MN, Dadi, Rachmawati J, Andrie BM, Aziz S, Mauladi MAR. 2026. Socio-economic and agroecological factors influencing sacha inchi productivity in West Java, Indonesia. Asian J Agric 10 (1): g100140. https://doi.org/10.13057/asianjagric/g100140. The high economic value of sacha inchi has attracted many farmers to cultivate it, despite the fact that it remains a relatively new crop with limited available information. We examined the effects socio-economic and agroecological factors on the sacha inchi productivity. The research was carried out using a survey based quantitative analysis involving 78 sacha inchi farmers in West Java Province, Indonesia, selected through a census approach. The data analyzed were primary data collected directly from respondents through structured interviews using questionnaires, in-depth interviews with key informants, and Focus Group Discussions (FGDs). Factors affecting the productivity of sacha inchi were analyzed using inferential statistics through a multiple linear regression model. The results at the 95% confidence level indicated that age, education, experience, family responsibility, soil acid, and altitude had a significant effect on sacha inchi productivity when tested simultaneously. Partially, age, education, soil acid, and altitude significantly influenced productivity, whereas farming experience and family responsibility did not have a significant effect. The novelty of this research resides in the comprehensive analysis of the interaction between farmers’ social conditions and the biophysical characteristics of land in determining sacha inchi productivity, an aspect that has been scarcely explored in prior studies.